Shifting the Blame: Storm and Wildfire Dramatic Images in American News Media - Aris Munandar; Amin Basuki (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2021)
Some media frames might be likely to seek to evoke a certain sentiment, and that natural disaster coverage by the media focuses on the current impact of disasters. In their coverage, American news media use polar sentiment words to create bleeding images of natural disasters, potentially counter-productive to the wisdom of dealing with the natural disaster. Identifying the sentiment words that lead to a misperception of natural disasters can help journalists adopt the wisdom that natural disasters are not a human enemy. The corpus-assisted discourse studies (CADS) reported in this article investigates the American media's issues for dramatic reporting and the polar sentiment words utilized in the framing. The corpus is built from 100 news articles reporting wildfires and storms by ten major online American news media published from January 1, 2018, through December 31, 2020. It uses AntConc to generate word-list and word-link from which it identifies the dominant issues. Subsequently, it compares the AntConc word-list with A List of Sentiment Words to reveal the tones and dramatic imaging. The findings show that the dominant issues in storm reporting are description, impact, and prediction, while wildfire reporting are cause, impact, action, and prediction. The negative polar words produce dramatic images of storm as a violent beast and wildfire as a vengeful invader. Such description is provocative to blaming natural disasters as a cause of human suffering rather than improving our behaviors to reduce the suffering. Thus, it is counter-productive to acquiring wisdom for dealing with natural disasters.